Value-driven business process management [ the value-switch for lasting competitive advantage - Franz, Peter; Kirchmer, Mathias , 1963- (New York : McGraw-Hill, 2012)
Value-Driven Business Process Management gives business leaders in any industry the rationale and methods for using BPM to gain clarity on how their business operates and develop the ability to put new ideas into action quickly. Readers learn how to redirect their focus from a "method-and-tool" view of BPM to a more broadly informed view of BPM as a management approach and put it to practical use to initiate action within their organization
1. Strategy and planning for value-driven BPM -- 2. Building a value-driven organization -- 3. The present and the future of value-driven bpm
Includes bibliographical references and index
Keywords: Business -- Data processing -- Management; Management information systems; Organizational effectiveness; Value analysis (Cost control)